(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The growing demand for accessible, efficient, and data-driven healthcare systems has encouraged the development of digital solutions addressing maternal and infant health challenges. In response, the researchers developed WOMB: A Web-Based System for Maternity Support and Infant Health Tracking with Integrated Data Analytics and Smart Algorithms, a platform designed to assist mothers and healthcare professionals in monitoring health data, improving record accuracy, and enhancing communication. The WOMB system is a centralized, user-friendly web platform that strengthens the management of maternal and infant healthcare. It provides essential functions such as tracking infant growth, scheduling medical appointments, managing health records, and offering educational resources for both mothers and healthcare workers. Through data analytics and intelligent algorithms, the system generates predictive insights, automates reminders, and supports evidence-based healthcare decisions. Built using PHP, MySQL, HTML, CSS, and JavaScript, the system complies with ISO/IEC 25010 Software Quality Standards to ensure security, usability, functionality, and performance efficiency. Its beneficiaries include mothers, infants, and healthcare providers, as it promotes improved health tracking, organized digital record management, and better access to critical information. ISO/IEC 25010 is an international software quality standard that defines attributes such as functionality, reliability, and usability to evaluate software effectiveness. This study utilized an Applied Research Design and adopted the Waterfall Model of the System Development Life Cycle (SDLC) to guide system creation and evaluation. The model involved six key phases—requirement analysis, system design, implementation, testing, deployment, and maintenance—to ensure structured and high-quality development. Data were collected through surveys, interviews, and observations from selected healthcare professionals and mothers to identify their needs and challenges in managing maternal and infant healthcare records. The Software Development Life Cycle (SDLC) is a structured process for planning, creating, testing, and deploying an information system efficiently. A total of 60 respondents participated in the system evaluation, consisting of 40 user respondents (mothers and healthcare providers) and 20 technical respondents (IT specialists and system developers). They assessed the system using the ISO/IEC 25010 Software Quality Model, focusing on the attributes of functionality, reliability, usability, efficiency, maintainability, portability, and security. Statistical tools such as the weighted mean were applied to analyze the results, which showed overall average means of 3.50 for user respondents and 3.63 for technical respondents—both interpreted as Strongly Agree. ISO/IEC 25010 is an international software quality standard that defines attributes such as functionality, reliability, and usability to evaluate software effectiveness. The evaluation results show that respondents found the system functional, secure, and easy to use for managing maternal and infant data. Usability received the highest rating among users, while functionality ranked highest among technical respondents. Although reliability obtained slightly lower ratings, it remained positive, suggesting only minor areas for improvement. Overall, the findings affirm that WOMB effectively meets international software quality standards and fulfills its purpose of promoting digital innovation in maternal and infant healthcare.